2022
DOI: 10.1111/echo.15304
|View full text |Cite
|
Sign up to set email alerts
|

The novel left atrial strain parameters in diagnosing of heart failure with preserved ejection fraction

Abstract: Objectives:We sought to evaluate the ability of the novel LA strain parameters to discriminate patients with heart failure with preserved ejection fraction (HFpEF) from individuals with risk factors of HFpEF. Methods and results:A total of n = 389 patients with risk factors for HFpEF finally was prospectively enrolled into the study, 66 of them were diagnosed with HFpEF by the 2021 ESC HF guidelines. Fifty-five patients were undergone left ventricular catheterization and simultaneous transthoracic echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…31,32 Novel parameters that describe LA stiffness could help differentiate between these two scenarios. 33,34 To improve the diagnostic accuracy of the existing guideline, new studies have confirmed the added value of parameters obtained with speckle tracking imaging. 35,36 We found that adding more ultrasound parameters to a multi-parameter algorithm to grade diastolic function led to a higher diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 Novel parameters that describe LA stiffness could help differentiate between these two scenarios. 33,34 To improve the diagnostic accuracy of the existing guideline, new studies have confirmed the added value of parameters obtained with speckle tracking imaging. 35,36 We found that adding more ultrasound parameters to a multi-parameter algorithm to grade diastolic function led to a higher diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…LA volume is related to LV filling pressure in adults but does not always track acute changes in LV filling pressure, and can represent both acute high inflow states and more chronic changes 31,32 . Novel parameters that describe LA stiffness could help differentiate between these two scenarios 33,34 …”
Section: Discussionmentioning
confidence: 99%
“…Atrial strain provides a parametric assessment of the atrium, including the reservoir, conduit and pump functions, and represents a novel and attractive ultrasound tool for the evaluation of diastolic dysfunction. Increased LV end-diastolic pressure relates to altered atrial mechanics, and the addition of left atrial strain to improve standard work-up of patients with suspected HFpEF has been hypothesized [72]. In CKD, the assessment of atrial strain provided added diagnostic and prognostic value [39], including association with major adverse cardiovascular events [40].…”
Section: Diastolic Functionmentioning
confidence: 99%
“…Therefore, echocardiography is needed to assess early changes in subclinical cardiac function in ESRD patients. [1][2][3] Evaluation of left atrial strain by speckle tracking imaging has been shown to play an important prognostic role in several different specific populations, [4][5][6][7] but there are few studies on evaluation of left atrial strain before and after single hemodialysis. Therefore, the present study compare the differences between pre-hemodialysis and normal controls, and the changes of echocardiography pre-and posthemodialysis, to investigate the influence of volume load on left atrial function.…”
Section: Introductionmentioning
confidence: 99%